Effect of seed treatment with tolchlofos-methyl on percentage incidence of seed-borne fungi and gernlination of rice (Oryza sativa) in Makurdi, Nigeria - EKEFAN, E J; IBRNENGE, I B and; VANGE, T (The Indian Journal of Agricultural Sciences, 2011)
Laboratory experiments were conducted between October 3002 and May 2003 to determine occurrence of seed-borne fungi and effect of seed treatment with tolchlofos-methyl(0.5,1 .O, 1.5 and 2.0s a i1litre)'on lice in Makurdi, Nigeria. Standard blotter method was used for assessment. Fungi detected were Sarocludium oryzae Aspetgillus niger, Rhizoctoia solani, Cercospora oryzae, Fusurium oxysporum, Fusurium moniliforme and Cercosporaki kuchii. Percentage occurrence of S. oryzae on varieties 'FH-308' and SIP1 (Local), A. niger on 'Pusa-Bas' and R. solani on 16-2608 was significantly (P=0.05) higher compared with other varieties. Each rate of tolchlofos-methyl tested significantly (P=0.05) reduced occurrence of R. solani, S, oryzae, A. niger C, kikucilii and C. oryzae and significalltly increased germination compared with the control. Germination was higher in 'PR-103' con-rpared with 'PR-I 12'. Incidence of fungi was negatively correlated with seed germination, although only those of S. otyzae (I=-- 0.55, P=0.05) and F. oxysporum (r= -0.39, P-0.05) were significant.